(untitled) (International Journal of Engineering and Computer Science, 2025)
This article examines the deployment of digital assistants to streamline auxiliary processes within industrial enterprises. Its relevance is driven by the Industry 4.0 transition and the imperative to improve responsiveness in maintenance, logistics management, and quality control. The study’s originality lies in aggregating insights on multifunctional use cases—voice, text, and multimodal systems—and in detailing their adaptation for production tasks. It outlines the principles governing assistant interactions with information systems and equipment, evaluates service-process speed and accuracy metrics, and explores barriers to implementation. Special emphasis is placed on a comparative analysis of modalities—voice dialogue, text chat, augmented reality—and their hybrid combinations. The research aims to assess functional capabilities, productivity impacts, and integration constraints. To this end, a comparative method and a systematic literature review were employed. The conclusions synthesize findings on efficiency improvements, downtime reduction, and future technology prospects. This work will support researchers and engineers in planning deployments of digital assistants and offers recommendations for tailoring solutions to diverse industry contexts.